Genetic knowledge and attitudes of parents of children with congenital heart defects. Issue 12 (24th September 2014) - Fitzgerald‐Butt, Sara M.; Klima, Jennifer; Kelleher, Kelly; Chisolm, Deena; McBride, Kim L.
<x xml:space="preserve">Abstract</x> Clinical genetic testing for specific isolated congenital heart defects (CHD) is becoming standard of care in pediatric cardiology practice. Both genetic knowledge and attitudes toward genetic testing are associated with an increased utilization of genetic testing, but these factors have not been evaluated in parents of children with CHD. We mailed a survey to measure the demographics, genetic knowledge, and attitudes towards genetic testing of parents of children with CHD who previously consented to participate in a separate research study of the genetic etiology of left ventricular outflow tract malformations (LVOT). Of the 378 eligible families, 190 (50%) returned surveys with both parents completing surveys in 97 (51%) families, resulting in 287 participants. Genetic knowledge was assessed on an adapted measure on which the mean percent correct was 73.8%. Educational attainment and household income were directly and significantly associated with genetic knowledge (P < 0.001). Attitudes about the health effects of genetic testing were favorable with at least 57% agreeing that genetic testing would be used for managing health care and finding cures for disease. Conversely, a minority of participants found it likely that genetic testing would be used for insurance (up to 39.9%), employment (15.8%), or racial/social discrimination (up to 11.2%). Parents of younger children were less likely to endorse employment or racial/social discrimination. Genetic knowledge was not correlated with specific attitudes. Among parents of children with CHD, genetic knowledge was directly associated with household income and education, but additional research is necessary to determine what factors influence attitudes towards genetic testing. © 2014 Wiley Periodicals, Inc.